Analyzing the Impact of Service Quality, Customer Satisfaction, Brand Image, and Customer Experience on Customer Loyalty - Djakaria, Merryta (APPS Publications, 2024)
Purposes - The purpose of this study is to analyze the relationships between service quality, customer satisfaction, brand image, customer experience, and their collective impact on customer loyalty. These factors are critical in understanding how businesses can maintain customer retention and loyalty in a competitive environment. Methodology - This study employed an empirical research approach, utilizing data collected through questionnaires distributed to 250 respondents. The data were analyzed using Partial Least Square (PLS) analysis through SMART PLS software. The study examined the significance of the relationships between the variables using t-statistics and p-value thresholds. Findings - The results of the analysis indicate that service quality, customer satisfaction, brand image, and customer experience all have a direct and significant impact on customer loyalty. Additionally, service quality also exerts an indirect influence on customer loyalty, mediated through customer satisfaction, brand image, and customer experience. Novelty - This study contributes to the existing literature by integrating the combined effects of service quality, customer satisfaction, brand image, and customer experience on customer loyalty, highlighting both the direct and indirect relationships. It reinforces the idea that enhancing service quality not only improves customer loyalty directly but also through the mediation of other key factors. Research Implications - The findings suggest that businesses should prioritize continuous improvements in service quality and focus on enhancing customer experience, satisfaction, and brand image to maintain and strengthen customer loyalty. These insights are valuable for business practitioners aiming to sustain competitive advantage through improved customer retention strategies.